Reaching Your Verdict: A Vocational Guide to Whether or Not to Study Law - Duperouzel, Lindsay (Thomson Reuters, 2018)
The Future of Australian Legal Education Conference was held in August 2017 to mark the 10th anniversary of the Australian Academy of Law (AAL), the 90th anniversary of the Australian Law Journal (ALJ) and the 30th anniversary of the Pearce ...